Study of corrosion rate and deposit accumulation under circulating water concentration in industrial applications - Чиченин, Вадим Валентинович; Кишневский, Виктор Афанасьевич; Грицаенко, Анастасия Сергеевна; Савич, Святослав Лаврентьевич; Шуляк, Ирина Дмитриевна (Eastern-European Journal of Enterprise Technologies, 2015)
The methods of investigating and the results of testing the corrosion rate and deposit accumulation on control samples of various metals in two similar industrial circulating cooling systems (CCS) with specified water chemistry were presented. As the make-up water, biologically treated municipal and industrial wastewater with a high content of anions of strong acids were used in systems. The results of the influence of phosphate inhibitors on the processes of deposit accumulation and corrosion rate at different concentration coefficients in the circulating cooling system were given. Introducing phosphate inhibitors to the make-up water, consisting of the biologically treated wastewater, subjected to liming allows to reduce the deposition rate on the heat transfer surface of heat exchangers to a value of 0.05 g/m2•h. Results of comparison of deposit accumulation and corrosion rate values on heated and unheated samples in the studied environments were provided. It was shown that the deposition rate on heated samples in comparable thermal-hydraulic conditions is several dozen times higher. The main factor affecting the value of deposit accumulation on samples from Art. 20 is the value of corrosion rate of the sample. To obtain reliable and reproducible results, laboratory and industrial tests of corrosion rate and deposit accumulation should be carried out for 1,000 hours or more in comparable thermal-hydraulic conditions on large-scale models of CCS at a given quality of circulating water.